Comparative Analytical Study for Determination of Acetylsalicylic Acid in Bulk and in Pharmaceutical Formulations - Mohammed, Sahar Samir (Al-Nahrain Journal of Science, 2013)
A new sensitive colorimetric method for determination of aspirin tablet in aqueous solution. The method is depending on the formation of a yellow colored azo dye by diazotization of 2, 4-dichloroaniline followed by azo-coupling reaction between the resulting product and acetylsalicylic acid. The lambda max of azo dye at 527nm. Beer’s low was found to be obeyed in the concentration range of 2-25µg/mL with rang of molar absorptivity between (2935) Lmol-1cm-1.Aspirin tablet from different sources industrial companies (SDI, NDI) using high performance liquid chromatography (HPLC) with reversed-phase (ODS-C18) column at low wave length of Uv-visible detection (280nm).the acetylsalicylic acid was eluted for 5 minute at flow rate 2ml/min. The retention time of acetylsalicylic acid was observed at 4.11 minutes. The concentration of the different above companies were gave good relationship between area under the peak (AUP) and acetylsalicylic acid content (p > 0.001). The comparing of the all values of aspirin tablets in (SDI, NDI) between the above methods were evaluated a good accuracy while the new colorimetric spectrophotometric method for the determination of acetylsalicylic acid (ASA) in pharmaceutical formulations developed procedure was successfully applied to the rapid determination of acetylsalicylic acid in commercial pharmaceutical preparations. The unique features of this procedure are that determination can be carried out at room temperature and analysis time is short. The newly developed method is simple, inexpensive and efficient for use in the analysis of a large number of samples.